Rapid and Facile Organic Ion-Associate Liquid-Phase Extraction and Spectrophotometric Quantification of Nitrite in Environmental Water Samples - Noriko Hata; Kazuki Minoshima; Kei Ito; Nozomi Kohama; Kazuto Sazawa; Sachiko Osada; Takuya Okazaki; Shigeru Taguchi; Hideki Kuramitz (Molecules)
Nitrite is a health and environmental hazard and pollutes water sources globally, but sensitive, rapid, and facile quantification methods are lacking. Herein, we report a method for extracting and quantifying low-concentration nitrite in surface water using minimal sample and solvent volumes. The nitrite reacted with sulfanilamide and N-1-naphthylethylenediammonium dichloride (NED), yielding an azo dye for extraction into an organic ion-associate liquid phase (IALP) formed in situ using ethylhexyloxypropylammonium and dodecyl sulfate ions. The addition of sodium acetate increased the pH, decreasing the cation charge from +2 to +1, improving extraction efficiency. Further, adding NaCl doubled the IALP volume, reduced the required standing time, and minimally affected absorbance, and adding concentrated HCl to the IALP enhanced the absorbance intensity via dye protonation. Crucially, the method achieved a 30-fold concentration factor compared to traditional pre-treatment methods, even without centrifugation, as well as a limit of detection of 0.09 µg NO2-N/L. Spiked recovery tests with river and seawater samples (93–103%) matched those of established methods. Digital imaging of IALP-extracted lake water yielded a limit of detection of 0.4 µg NO2-N/L. The method is a sensitive, efficient approach for nitrite detection, enabling rapid environmental monitoring via spectrophotometry and digital imaging.